Selected Algorithmic Papers from the International Workshop on Combinatorial Algorithms 2024 - Adele Anna Rescigno (Algorithms, 2025)
This Special Issue is dedicated to a selection of papers from the 35th International Workshop on Combinatorial Algorithms (IWOCA 2024), held in July 2024, in Ischia, Italy, with Adele A [...]